Penerjemahan pada Novel Anak dalam Bahasa Inggris ke Bahasa Indonesia - Youlinda, Friza (LANCAH: Jurnal Inovasi dan Tren, 2025)
The translation of children's novels is a complex process, as it is essential to convey the messages and values from the source text in a manner that is accessible to young readers. This study aims to identify the translation strategies employed and the challenges faced in translating children's literature. The methodology includes text analysis of one or two children's novels in English and their translations into Indonesian, along with interviews with translators to gain insights into their practices and considerations during the translation process. The main findings indicate that cultural differences and language style are key factors influencing translation quality. Translators often encounter challenges when translating cultural elements, humor, and idioms that lack direct equivalents in the target language. Strategies such as domestication and adaptation of language style prove effective in maintaining the relevance of the story for young readers. Additionally, collaboration with local cultural experts and the use of glossaries or footnotes can help address these challenges. This research underscores the importance of a holistic approach to translating children's literature to enhance cultural understanding and literacy among younger generations.